Towards a european public sphere? Vertical and horizontal dimensions of europeanised political communication - Ruud Koopmans; Jessica Erbe (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
In this paper, we develop a systematic approach to Europeanisation of the public sphere, distinguishing three forms of Europeanisation of public political communication: supranationally, vertically and horizontally. These forms materialise through communicative linkages between political actors of different geographical spheres (e.g., from the own country, other countries or the EU level) in national mass media. Based on a political claims analysis in seven policy fields for the year 2000, we determine the degree in which these forms of Europeanisation are actually present in the German press. Our findings challenge, at least partially, the wide-spread idea of a public sphere deficit in the European Union: Europeanisation of public political communication appears to vary considerably between policy fields, and in fields with a clear-cut transfer of competencies to the supranational level, public discourse in the mass media seems to follow suit. – – In diesem Papier entwickeln wir einen systematischen Ansatz zur Europäisierung der Öffentlichkeit, der drei Formen von europäisierter politischer Kommunikation unterscheidet: supranational, vertikal und horizontal. Diese Formen kommen durch kommunikative Verbindungen zwischen politischen Akteuren verschiedener geographischer Räume (z.B. aus dem eigenen Land, anderen Ländern oder der EU Ebene) in nationalen Massenmedien zustande. Mittels einer politischen Claim-Analyse in sieben Politikfeldern für das Jahr 2000 stellen wir fest, in welchem Umfang diese Formen von Europäisierung in der deutschen Presse tatsächlich vorhanden sind. Unsere Ergebnisse stellen zumindest teilweise die weit verbreitete These des Öffentlichkeitsdefizits in der Europäischen Union in Frage: Die Europäisierung der politischen Kommunikation variiert erheblich je nach Politikfeld, und in Bereichen mit klarer Kompetenzübertragung zur supranationalen Ebene scheint der öffentliche Diskurs in den Massenmedien durchaus nachzuziehen.
Keywords: 300